3(3+2x)-5=40

Simple and best practice solution for 3(3+2x)-5=40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3+2x)-5=40 equation:


Simplifying
3(3 + 2x) + -5 = 40
(3 * 3 + 2x * 3) + -5 = 40
(9 + 6x) + -5 = 40

Reorder the terms:
9 + -5 + 6x = 40

Combine like terms: 9 + -5 = 4
4 + 6x = 40

Solving
4 + 6x = 40

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 6x = 40 + -4

Combine like terms: 4 + -4 = 0
0 + 6x = 40 + -4
6x = 40 + -4

Combine like terms: 40 + -4 = 36
6x = 36

Divide each side by '6'.
x = 6

Simplifying
x = 6

See similar equations:

| 3(f-3)=-6 | | -8(s+3)=-36 | | 39+6= | | 8(4s+5)=168 | | whatdoesk= | | 9n+8= | | (x^1/4*z^4/5)^-2 | | 7x-7x+6y=3 | | (x^1/4*2^4/5)^-2 | | (x^1/4*2^4/8)^-2 | | 6x+5=414 | | 5x+5=41 | | _6x2_5x+4=0 | | v*(8vu^2)^1/2)-3u(50v^3)^1/2 | | 8g-8+2g+6= | | 42^3/3x=2 | | 4x+6-2y=14 | | 4x-10+10y=7y-2x | | -x^2-8x=1 | | 10x-9=3x+8+6x | | x=65y^2+10y | | 31n(x-7)=6 | | 3x+86=10x-5 | | -3x=9.4 | | 7x-14=9-3x | | y(t)=x(t-1)+x(t+1) | | X+X*.06=260 | | kx^2-2x-7=0 | | X*.06=260 | | 11x-4=6x+10 | | 10=110 | | -x^2-14x+14=0 |

Equations solver categories